Case Report: Metastatic colorectal cancer with ALK–CEP44 fusion and rapid resistance development - Hofmann, Silvan; Egger, Claudine; Potthast, Silke; Zoche, Martin; Wicki, Andreas; Mehra, Tarun (Frontiers in Oncology, 2025)
BackgroundColorectal cancer rarely harbors rearrangements in the ALK gene, and the therapeutic significance of non-canonical or functionally unclear ALK fusions remains poorly defined. We report a case of metastatic CRC with an ALK–CEP44 fusion not previously described in this tumor type, associated ALK overexpression, a notable clinical response to the ALK inhibitor alectinib, and rapid development of multiple ALK resistance mutations.Case SummaryA 60-year-old male patient was diagnosed with stage IIIA right-sided CRC. Six months after adjuvant chemotherapy, he developed liver metastases. Comprehensive molecular profiling revealed strong ALK expression, a novel ALK–CEP44 fusion predicted to lack a functional kinase domain, and additional ALK alterations. Palliative chemotherapy induced a temporary response. Upon progression, treatment with alectinib led to rapid clinical, radiological and biochemical improvement. However, disease progression recurred shortly thereafter, and next-generation sequencing revealed four resistance-associated ALK mutations. The patient ultimately died due to progressive liver failure.ConclusionALK-targeted therapy may provide benefit in selected CRC cases with atypical ALK alterations, even when the oncogenic role is uncertain. Comprehensive molecular profiling and timely therapeutic decisions are essential in managing such rare and complex cases.